Impact of Leadership Styles, Proprietorship and Funding on Administrators’ Effectiveness in Universities in the South-West, Nigeria (2015)
Optimum performance of the university system is dependent on decision-making, teamwork, planning, control, coordination and communication system, which are measures of effectiveness of the administrators. There are evidences that administrators‟ work schedule in the Nigerian university system had been hampered by internal and external interferences; a trend that had raised concerns among stakeholders. Previous studies have focused on the effects of financial, environmental, institutional and governmental factors with little or no consideration for the combined influence of leadership styles, proprietorship, and funding on administrators‟ effectiveness. This study, therefore, determines the impacts of leadership styles, proprietorship and funding on administrators‟ effectiveness in universities in South-West Nigeria. The descriptive survey design was adopted. The purposive sampling technique was used to select five universities; one each of: state, private, generalised federal university, federal university of technology and federal university of agriculture. The technique was also used to select 30 Principal Officers, 54 Deans/Provosts, 242 Heads of Departments/Directors of Units and 194 Deputy Registrars/Deputy Bursars/Deputy Librarians/Faculty Officers from the five selected universities. Leadership Style (r=0.95), Proprietorship (r=0.98) and Funding (r=0.99) Scales and Administrators‟ Effectiveness Questionnaire (r=0.98) were used for data collection. These were complemented with In-depth Interview with 20 selected university administrators. Four research questions were answered and three hypotheses tested at 0.05 level of significance. Data were analysed using descriptive statistics, Pearson product moment correlation, multiple regression and content analysis. The three predisposing factors had a joint impact on administrators‟ effectiveness in the universities (F(6,1468)=15546.92, R=.99), and accounted for 98.5% in the variance of administrators‟ effectiveness. Proprietorship (β=.53), funding (β=.42) and leadership styles (β=.20) had relative contributions to administrators‟ effectiveness. Components of proprietorship, namely: federal (r=.53), state (r=.23), and private (r=.98) correlated with administrators‟ effectiveness. Also, democratic (r=.94), autocratic (r=.92) and laissez faire (r=.90) leadership styles correlated with administrators‟ effectiveness. Funding sources namely: government subvention (r=.76), internally generated revenue (r=.77), endowments (r=.80), donations (r=.79) and tuition (r=.77) correlated with administrators‟ effectiveness. The three predisposing factors significantly impacted on administrators‟ effectiveness as follows: decision-making (r=.75), teamwork (r=.80), planning (r=.78), control (r=.77), coordination (r=.65), and communication system (r=.05). There existed a difference in administrative effectiveness on the proprietorship: federal (x̅=20.98), state (x̅=16.53), and private (x̅=12.70). Differences were noted in the perception on administrative effectiveness among the Principal Officers, their Deputies, academic heads and Directors of Units. Democratic leadership styles, private proprietorship and endowment funding impacted positively on administrators‟ effectiveness in universities in the South-West, Nigeria. To ensure improved administrators‟ effectiveness in the universities, there is a need for application of democratic leadership style, freedom from proprietors‟ interference and adequate funding.